Reading in Communication Perspective - Fatimah, Angggun Nadia (UI Scholars Hub, 2020)
As a part of daily activities, the concept of reading is often used without referring to its conceptual meaning. The meaning of reading is simplified, to be only associated with the activity of scanning textual literatures. This simplified meaning does not only occur in the context of popular conversation, but can also be found in academic literature. By utilizing the literature review method, this conceptual article seeks to find a more relevant definition of reading that can explain the activity of reading in a communication perspective, especially related to the development of communication technology. Result of this study shows that the concept of reading in the field of communication is not limited to written script reading. In communication perspective, reading is more properly seen as an activity of scanning codes, symbols, and other forms of representation that contain patterns, including written scripts. Data and information can be seen as messages, while the five senses and technology as an extension of the sensory system,can be seen as sensors that receive the messages.